Observed to expected lung area to head circumference ratio (O/E LHR) in fetuses with congenital anomalies of the kidney and urinary tract (CAKUT): assessment and evaluation as predictive factor for acute postnatal outcome—a single center study - Sourouni, M.; Haisch, L.; Oelmeier, K.; Möllers, M.; Willy, D.; Sondern, K.; Köster, H.; Steinhard, J.; Sandkötter, J.; Klockenbusch, W.; Schmitz, R.; Potratz, J. (Frontiers in Pediatrics, 2023)
Introduction To assess the observed to expected lung area to head circumference ratio (O/E LHR) in fetuses with congenital anomalies of the kidney and urinary tract (CAKUT) and to explore its value as a potential predictive factor for postnatal outcome. Methods A retrospective single-center study was conducted on pregnancies complicated by CAKUT between 2007 and 2018. The lung-to-head ratio (LHR) was calculated for each fetus by two independent observers. Correlations between O/E LHR and various perinatal outcome factors were assessed with Spearmanʼs rank correlation. Furthermore, nominal logistic regression was performed to assess O/E LHR as predictive factor for respiratory distress in newborn. Results Of 64 pregnancies complicated by CAKUT, 23 were terminated. In the 41 cases of continuation of pregnancy, newborn presenting respiratory distress with need for respiratory support in the delivery room showed earlier gestational age at onset of amniotic fluid abnormalities and at birth. Although median O/E LHR and median single deepest pocket (SDP) of amniotic fluid were significantly smaller in newborn that did develop respiratory distress with need of respiratory support in the delivery room, neither O/E LHR nor SDP were accurate predictors for the development of respiratory distress. Conclusions Our data show that O/E LHR alone cannot serve as a predictive marker for fetal outcome in pregnancies complicated by CAKUT, though it might still be a helpful parameter together with detailed renal ultrasound evaluation, onset of amniotic fluid abnormality and SDP, particularly in its extreme values.